Identification of eight novel proteasome variants in five unrelated cases of proteasome-associated autoinflammatory syndromes (PRAAS) - Papendorf, Jonas Johannes; Ebstein, Frédéric; Alehashemi, Sara; Piotto, Daniela Gerent Petry; Kozlova, Anna; Terreri, Maria Teresa; Shcherbina, Anna; Rastegar, Andre; Rodrigues, Marta; Pereira, Renan; Park, Sophia; Lin, Bin; et al. (Frontiers in Immunology, 2023)
Mutations in genes coding for proteasome subunits and/or proteasome assembly helpers typically cause recurring autoinflammation referred to as chronic atypical neutrophilic dermatosis with lipodystrophy and elevated temperatures (CANDLE) or proteasome-associated autoinflammatory syndrome (PRAAS).Patients with CANDLE/PRAAS present with mostly chronically elevated type I interferon scores that emerge as consequence of increased proteotoxic stress by mechanisms that are not fully understood.Here, we report on five unrelated CANDLE/PRAAS patients carrying novel inherited proteasome missense and/or nonsense variants. Four patients were compound heterozygous for novel pathogenic variants in the known CANDLE/PRAAS disease genes, PSMB8 and PSMB10, while one patient showed additive loss-of-function mutations in PSMB8, and in 2 previously not associated disease genes, PSMA5 and PSMC5. Our in vitro investigations provide evidence on the pathogenicity of these variants. All newly identified mutations substantially impact the steady-state expression of the affected proteasome subunits and/or their incorporation into mature 26S proteasomes. Our observations expand the spectrum of PRAAS-causing genetic variants and improve a molecular diagnosis and genetic counseling of patients with sterile autoinflammation.